Determinan Kepatuhan Wajib Pajak PBB-P2 di Desa Brambang, Kecamatan Diwek, Kabupaten Jombang - Vella Angelia Pramesti; Dyah Ratnawati (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of income levels, tax knowledge, tax penalties, and tax rates on PBB-P2 taxpayer compliance in Brambang Village, Diwek Subdistrict, Jombang Regency. This quantitative research involved 97 participants selected via simple random sampling from a total population of 2,929 taxpayers, utilizing structured questionnaires for primary data collection. Data analysis was systematically conducted through structural equation modeling utilizing SmartPLS version 4 software. The structural model evaluation shows that the coefficient of determination contribution reaches 0.430, indicating a moderate predictive relevance. Empirical results demonstrate that taxpayer income and tax penalties significantly affect tax compliance behavior. Conversely, tax knowledge and tax rates do not show any significant influence in this context. These findings imply that community financial conditions and strict penalty enforcement are the primary drivers of compliance. Consequently, local governments along with related agencies can utilize these valuable insights to formulate firmer, highly targeted, and more consistent tax collection strategies to optimize PBB-P2 revenue sustainably.